How can animal disease risks be better managed? - Carpenter, T.E.; Rich, Karl M. (Wiley, 2012)
Livestock farming is imbued with a variety of disease-related risks. The threat of disease, and actions taken (or not taken) to mitigate it, can impact both the broader livestock sector and potentially society at large if the disease is what is termed zoonotic i.e. impacting both animal and human health alike. Understanding the nature of these risks is crucial to improve policymaking and requires multidisciplinary toolkits. In this article we identify various frameworks from economics and epidemiology to analyze the impact of animal disease risks in livestock environments. From this, we examine the policy responses implemented to better manage risk, and conclude by identifying the current gaps in the decision process related to risk and uncertainty, which is a reflection of imperfect knowledge. Recent advances in our modeling frameworks have helped streamline the complex decision space faced by policymakers and improved our understanding of the risks and consequences of mitigation strategies. At the same time, while there has been significant progress in integrating economic and epidemiological tools to analyze risk, more work is required to understand the feedbacks between disease and behaviour taken to control it.